Assessment of hemodynamic disturbances and impaired ventricular filling in asymptomatic fontan patients: A 4D flow CMR study - Li-Wei Hu; Xiaodan Zhao; Shuang Leng; RongZhen Ouyang; Qian Wang; Ai-Min Sun; Yi-Man Liu; Wei Dong; Liang Zhong; Yu-Min Zhong (European Journal of Radiology Open)
Background: The Fontan procedure is a surgical intervention designed for patients with single ventricle physiology, wherein the systemic venous return is redirected into the pulmonary circulation, thereby facilitating passive pulmonary blood flow without the assistance of ventricular propulsion. Consequently, long-term follow-up of individuals who have undergone the asymptomatic Fontan procedure is essential. Objectives: The aims of this investigation were to: 1) examine the impact of flow components and kinetic energy (KE) parameters on hemodynamic disturbances in asymptomatic Fontan patients and control group; 2) Assess left ventricular diastolic dysfunction through the analysis of 4D flow parameters across different Fontan sub-groups; 3) Compare intracardiac flow parameters among Fontan sub-groups based on morphological features of the left ventricle (LV) and right ventricle (RV). Methods: Twenty-five Fontan patients (mean age: 10 ± 3 years, male/female: 15/10) and fourteen control subjects (mean age: 10 ± 2 years, male/female: 8/6) were recruited retrospectively for the study. The Fontan patients were further categorized into three groups based on their ventricular function: left ventricular (LV), right ventricular (RV), and biventricular (BiV). Each participant underwent cardiovascular magnetic resonance (CMR) imaging, including cine and 4D flow sequences on a 3.0 T scanner. Ventricular flow components and KE were assessed using 4D flow. The study utilized cine images to analyze cardiac function and inter-ventricular mechanical dyssynchrony. Echocardiography evaluated functional ventricular diastolic dysfunction. Results: Fontan patients had a higher median functional single ventricle (FSV) residual volume compared to controls (28 % vs. 23 %, P = 0.034), with lower median FSV direct flow (32 % vs. 40 %, P = 0.005) and delayed ejection flow (17 % vs. 24 %, P = 0.024). The parameters of FSV normalized to the ventricular end-diastolic volume (KEiEDV) were found to be significantly lower in Fontan patients (all P < 0.05). In both left ventricle (LV) and biventricular (BiV) Fontan subgroups, direct flow was identified as an independent predictor of LV diastolic dysfunction (AUC=0.76, Sensitivity=86 %, Specificity=70 %). Furthermore, residual volume and E-wave KEiEDV were observed to be significantly different between LV and right ventricle (RV) Fontan subgroups. Conclusions: The altered flow pattern and reduced kinetic energy observed in Fontan patients may indicate hemodynamic disturbances and compromised ventricular filling. Reduced direct flow is associated with LV diastolic dysfunction in LV and BiV Fontan subgroups. Systemic LV exhibited a more efficient intracardiac flow pattern compare with systemic RV in Fontan patients.